Classification and Taxonomy of Vegetable Macergens - Aremu, Bukola R.; Babalola, Olubukola O. (Frontiers in Microbiology, 2015)
Macergens are bacteria capable of releasing pectic enzymes (pectolytic bacteria). These enzymatic actions result in the separation of plant tissues leading to total plant destruction. This can be attributed to soft rot diseases in vegetables. These macergens primarily belong to the genus Erwinia and to a range of opportunistic pathogens namely: the Xanthomonas spp, Pseudomonas spp., Clostridium spp., Cytophaga spp. and Bacillus spp. They consist of taxa that displayed considerable heterogeneity and intermingled with members of other genera belonging to the Enterobacteriaceae. They have been classified based on phenotypic, chemotaxonomic and genotypic which obviously not necessary in the taxonomy of all bacterial genera for defining bacterial species and describing new ones These taxonomic markers have been used traditionally as a simple technique for identification of bacterial isolates. The most important fields of taxonomy are supposed to be based on clear, reliable and worldwide applicable criteria. Hence, this review clarifies the taxonomy of the macergens to the species level and revealed that their taxonomy is beyond complete. For discovery of additional species, further research with the use modern molecular methods like phylogenomics need to be done. This can precisely define classification of macergens resulting in occasional, but significant changes in previous taxonomic schemes of these macergens.